Cigarette smoking in young-adult workers: a cross-sectional analysis from Abruzzo, Italy (Italian Journal of Public Health, 2010)
Background: The “Valentino” cross-sectional study is aimed at evaluating the prevalence and pattern ofcigarette smoking according to occupational group in a representative sample of workers aged 18-35 yearsfrom Abruzzo, Italy.Methods: Randomly selected workers anonymously self-compiled a structured questionnaire containingvalidated items. Job type was coded according to the International Standard Classification of Occupations.Results: The sample consisted of 3989 workers. Current smoking prevalence was 45.9%, varying acrossoccupational groups and ranged from 37.2% among clerical support workers, up to 57.1% among craft,agricultural and fishery sector workers. After controlling for several potential confounders using logisticregression, craft, agricultural, forestry and fishery workers (adjusted odds ratio 1.65; 95% confidence intervals1.21-2.27), and call-center operators (1.91; 1.44-2.53) were significantly more likely to be current smokers thanprofessionals and clerical or support workers. Interestingly, when alcohol and cannabis use were included inmultivariate analysis, the association between smoking and gender was no longer significant.Conclusions: An independent association was found between specific occupational classes and tobaccosmoking, suggesting occupation type should be considered in prioritizing subsets of populations towardswhich smoking cessation campaigns should be targeted first.
Keywords: cigarette smoking; young-adult workers; occupational groups; Italy